Effects of computer-based cognitive rehabilitation on working memory in patients with acquired brain injury in the chronic phase, a pilot-study. (21st March 2022) - Svaerke, Katrine; Pyke, Sandra Bruhn; Tjoernlund, Morten; Humle, Frank; Mogensen, Jesper
ABSTRACT: Background: Working memory impairment is common in patients in the chronic phase after acquired brain injury (ABI), and there is a need to develop efficacious rehabilitation methods. This trial explored the effects of two different computer-based cognitive rehabilitation (CBCR) programmes on working memory in the chronic phase after ABI, as well as the role of continuous support versus no support from a health professional on the efficacy of CBCR. Methods: A total of 72 patients were randomized into four different groups for a 12-week intervention: Two groups trained with the CBCR-programmes 'Cogmed' and 'Brain+ Health, ' respectively, and one group completed active-control training. All three groups received continuous support from a health professional. The last group trained with the CBCR programme 'Brain+ Health' but received no support. Before and after the intervention, patients were tested with a neuropsychological battery of working memory, attention and executive functions. Results: Both CBCR-programmes improved working memory when administered with support from a health professional. The programmes improved different sub-components of working memory, possibly because of their individual content and design. None of the CBCR-programmes were more efficacious than sham-training with support. CBCR without support did not improve working memory in patients.